(untitled) (Al-Academy, 2025)
This research addresses one of the most important acting styles in theatre, namely the classical style of performance, which has been used by many Iraqi directors in their theatrical performances. To define this acting style, the researchers used the performance of actor Taama Al-Tamimi as a model for analysis. This model aims to identify the classical acting style in Iraqi actors’ performances. The research included an introduction and a theoretical foundation that included (the art of acting according to curricula, the classical acting style, and the elements of actor Taama Al-Tamimi’s performance). The researchers then developed a method for measuring actor performance in classical theatre. In the research procedures, the researchers used the play "Gilgamesh" as a deliberate sample. After analysing the sample, the researchers reached a set of results, including Al-Tamimi embodied the character using organized tonal diction and controlled theatrical movement, reflecting a deep understanding of the characteristics of the classical style, which is based on sobriety and physical and vocal discipline. A set of conclusions, including Al-Tamimi utilized his strong tone and physical height to highlight the heroic or noble dimensions of the character, as required by the classical style.